Bird Observations in Severnaya Zemlya, Siberia - de Korte, J.; Volkov, A.E.; Gavrilo, M.V. (ARCTIC, 1995)
Fieldwork in different parts of Severnaya Zemlya in 1985, 1991, 1992 and 1993 and aerial surveys in 1994 revealed a limited bird fauna with a total of 17 breeding species. The most numerous breeding birds are cliff-nesting seabirds, comprising little auk (Alle alle), 10 000-80 000 pairs; kittiwake (Rissa tridactyla), 5000-10 000; black guillemot (Cepphus grylle), 1000-5000; ivory gull (Pagophila eburnea), 1000-2000; and glaucous gull (Larus hyperboreus), 500-1000. They breed all over the archipelago, usually in rather small mixed- or single-species colonies. Arctic tern (Sterna paradisaea) 100-500, and herring gull (Larus argentatus) 1-10, breed as solitary pairs or with a few pairs together. Of tundra birds, only brent goose (Branta bernicla), purple sandpiper (Calidris maritima) and snow bunting (Plectrophenax nivalis) are found breeding on most of the major islands. The other tundra species--red-throated diver (Gavia stellata), king eider (Somateria spectabilis), sanderling (Calidris alba), Arctic skua (Stercorarius parasiticus), long-tailed skua (Stercorarius longicaudus), snowy owl (Nyctea scandiaca) and Lapland bunting (Calcarius lapponicus)--breed in small numbers and in limited areas, often not every year. Of the even fewer mammal species, reindeer (Rangifer tarandus) occurs occasionally, while Arctic fox (Alopex lagopus) and collared lemming (Dicrostonyx torquatus) are locally common in some years.Key words: Severnaya Zemlya, high Arctic birds, breeding distribution Des études sur le terrain menées dans différentes parties de la Severnaïa Zemlia en 1985, 1991, 1992 et 1993 ainsi que des relevés aériens effectués en 1994 ont révélé une avifaune limitée comptant au total 17 espèces reproductrices. Les oiseaux nicheurs les plus nombreux sont ceux nichant sur les falaises. Ils comprennent le mergule nain (Alle alle) [10 000 à 80 000 paires]; la mouette tridactyle (Rissa tridactyla) [5000 à 10 000]; le guillemot à miroir (Cepphus grylle) [1000 à 5000]; la mouette blanche (Pagophila eburnea)[1000 à 2000]; ...